2013
DOI: 10.1002/jmv.23643
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in the Maghreb region

Abstract: Hepatitis C is a global health problem with a worldwide prevalence of about 3% (around 170 million people). Hepatitis C virus (HCV) is major concern in the Maghreb countries, Algeria, Libya, Mauritania, Morocco, and Tunisia, but no detailed description of its epidemiology in the region is available. In the present review, a systematic search was undertaken covering HCV data available in peer-reviewed databases as well as institutional reports and regional conference meeting abstracts from the Maghreb countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
6
11
1
Order By: Relevance
“…Among HCV‐infected patients, 69.1% were infected with HCV genotype 1, whereas the remaining were infected with genotype 2 (30.9%). In line with previous reports, HCV subtype 1b was strongly predominant …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Among HCV‐infected patients, 69.1% were infected with HCV genotype 1, whereas the remaining were infected with genotype 2 (30.9%). In line with previous reports, HCV subtype 1b was strongly predominant …”
Section: Resultssupporting
confidence: 93%
“…This signal peptide variation may affect secretion and translocation efficiencies, posttranslational processing, localization, quality, and thus the functionality of the affected protein . In addition, previous studies reported that the presence of the rs179008 variant was predictive of an unfavourable outcome of IFN‐α therapy, and that the carriage of TLR7 Gln11Leu variant genotype was linked to higher viral loads, accelerated progression to advanced immune suppression, and increased HIV‐1 susceptibility in females . Indeed, it was found that peripheral blood mononuclear cells from carriers of this polymorphism secreted significantly less IFN‐α upon TLR7 activation …”
Section: Discussionmentioning
confidence: 99%
“…Genotype 1 is the most common HCV genotype consistently reported for most countries in the Maghreb [ 99 , 100 ]. According to a study by Messina et al ., HCV genotype 1 accounts for 82% of HCV infections in Algeria, 44% of infections in Libya, 74% of infections in Morocco, and 41% of infections in Tunisia [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, we detected minor factual errors in Gower et al ., the estimate for Benin [3.6% (3.6; 12.8)] being based on two studies conducted in Nigeria , and the estimates for Algeria [1.4% (0.2; 2.5)] and Mauritania [1.9% (1.1; 10.7)] being based on a previous review from Ezzikouri et al . that included studies published before 2000, hence in contradiction with the inclusion criteria in Gower et al .…”
Section: Discussionmentioning
confidence: 99%